CO2 Activation with Formation of Uranium Carbonate Complexes in a Closed Synthetic Cycle - Waldschmidt, Pablo; Hörger, Christopher; Riedhammer, Judith; Heinemann, Frank Wilhelm; Hauser, Christina; Meyer, Karsten (Organometallics, 2020)
A closed synthetic cycle for the transformation of carbon dioxide to carbonate with a mid-valent tris(aryloxide)-ligated uranium(IV) terminal oxo complex is presented herein. Starting from the previously reported uranium(III) complex, [UIII(OArAd,Ad,Me)3], the uranium(V) terminal oxo complex, obtained by oxidation with N2O or NO, can be reduced with KC8 to yield CO2 activating anionic uranium(IV) oxo complexes [(Ad,Ad,MeArO)3UIV(O)]-. The cycle proceeds with the formation of [(Ad,Ad,MeArO)2(κ2-Ad,Ad,MeArOCO2)UIV(μ-κ1:κ2-CO3)]- upon reaction of the oxo anion with excess CO2 that adds to the terminal oxido ligand and inserts into the uranium-aryloxide bond. Treating this complex with trimethylsilyl halide eliminates both carbonates and generates, for instance, [K(2.2.2-crypt)][(Ad,Ad,MeArO)3UIV(I)2], which can ultimately be reduced with KC8 to recover the trivalent starting material, thus closing the cycle. In contrast, reaction of the 18-crown-6 stabilized U(IV) oxo analogue with CO2 yields a rare and isolable example of a uranium complex with a μ-κ1:κ2-CO3-bound carbonate weakly interacting with the [K(18-crown-6)(THF)]+ moiety; here, CO2 insertion and formation of an aryl carbonate ligand are not observed.
CRIS-Team Scopus Importer:2020-02-04

Homoleptic Acetylacetonate (acac) and ?-Ketoiminate (acnac) Complexes of Uranium - Waldschmidt, Pablo; Riedhammer, Judith; Hartline, Douglas; Heinemann, Frank Wilhelm; Meyer, Karsten (Inorganic Chemistry, 2023)
Transmetalation of potassium salts of differently substituted acetylacetonate (acac) and beta-ketoiminate (acnac) with [U(I)3(dioxane)1.5] and [U(I)4(dioxane)2] resulted in the formation of homoleptic, octahedral complexes [U(tBuacnacPh)3] (with tBuacnacPh = 2,2,6,6-tetramethyl-5-(phenylimino)heptan-3-onate) in the oxidation states +III and +IV and the homoleptic, square prismatic complexes [UIV(MeacnacPh)4] (with MeacnacPh = 4(phenylimino)pentan-2-onate) and the homoleptic, square anti prismatic complexes [U(tBuacac)4] [with acac = 2,2,6,6-tetramethyl3,5-heptanedionate (tBuacac), 2,2,6,6-tetramethyl,4-methyl-3,5-heptanedionate (tBuacMeac), and 2,2,6,6-tetramethyl-4-phenyl-3,5-heptanedionate (tBuacPhac)] in oxidation states +III, +IV, and +V. Oxidation of [UIII(tBuacnacPh)3] (1) with AgOTf yielded [UIV(tBuacnacPh)3][OTf] (2), which was fully characterized by single-crystal X-ray diffraction analysis, a combination of ultraviolet/visible/near-infrared, nuclear magnetic resonance, and infrared spectroscopies, and solid-state superconducting quantum interference device magnetization studies. Complexation of the sterically less encumbering ligand derivative MeacnacPh provided access to the tetravalent, square antiprismatic complex [UIV(MeacnacPh)4] (3). Cyclovoltammetric analysis of the square antiprismatic [UIV(tBuacac)4] (4), [UIV(tBuacMeac)4] (5), and [UIV(tBuacPhac)4] (6) revealed reversible anodic and cathodic waves, attributable to the U(III/IV) and U(IV/V) redox couples, both being chemically accessible, as tested in the case of 5. The corresponding U(III) and U(V) compounds, [K(2.2.2-cryptand)][UIII(tBuacMeac)4] (7) and [UV(tBuacMeac)4][SbF6] (8), were synthesized accordingly. Unfortunately, reduced 7 proved to be too reactive for isolation and could only be detected by electron paramagnetic resonance spectroscopy. Notably, electrochemical studies on homoleptic uranium(IV) complexes with differently derivatized (R) acRac ligands (R = H, Me, or Ph) feature large electrochemical windows of up to 2.91 V, measured between the uranium(III) and the uranium(V) species, in addition to high stability toward repeated potential scans.
CRIS-Team WoS Importer:2023-03-03

Nonaqueous Electrochemistry of Uranium Complexes: A Guide to Structure-Reactivity Tuning - Riedhammer, Judith; Halter, Dominik P.; Meyer, Karsten (Chemical Reviews, 2023)
Uranium complexes can be stabilized in a wide range of oxidation states, ranging from UII to UVI and a very recent example of a UI complex. This review provides a comprehensive summary of electrochemistry data reported on uranium complexes in nonaqueous electrolyte, to serve as a clear point of reference for newly synthesized compounds, and to evaluate how different ligand environments influence experimentally observed electrochemical redox potentials. Data for over 200 uranium compounds are reported, together with a detailed discussion of trends observed across larger series of complexes in response to ligand field variations. In analogy to the traditional Lever parameter, we utilized the data to derive a new uranium-specific set of ligand field parameters UEL(L) that more accurately represent metal-ligand bonding situations than previously existing transition metal derived parameters. Exemplarily, we demonstrate UEL(L) parameters to be useful for the prediction of structure-reactivity correlations in order to activate specific substrate targets.
CRIS-Team WoS Importer:2023-05-26

Werner-Type Complexes of Uranium(III) and (IV) - Riedhammer, Judith; Aguilar-Calderón, J. Rolando; Miehlich, Matthias; Halter, Dominik; Munz, Dominik; Heinemann, Frank Wilhelm; Fortier, Skye; Meyer, Karsten; Mindiola, Daniel (Inorganic Chemistry, 2020)
Transmetalation of the β-diketiminate salt [M][MenacnacPh] (M+ = Na or K; MenacnacPh- = PhNC(CH3)2CH-) with UI3(THF)4 resulted in the formation of the homoleptic, octahedral complex [U(MenacnacPh)3] (1). Green colored 1 was fully characterized by a solid-state X-ray diffraction analysis and a combination of UV/vis/NIR, NMR, and EPR spectroscopic studies as well as solid-state SQUID magnetization studies and density functional theory calculations. Electrochemical studies of 1 revealed this species to possess two anodic waves for the U(III/IV) and U(IV/V) redox couples, with the former being chemically accessible. Using mild oxidants, such as [CoCp2][PF6] or [FeCp2][AlOC(CF3)34], yields the discrete salts [1][A] (A = PF6-, AlOC(CF3)34-), whereas the anion exchange of [1][PF6] with NaBPh4 yields [1][BPh4].
CRIS-Team Scopus Importer:2020-02-28